2022
DOI: 10.1017/s0033291722002677
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of repetitive negative thinking in depression is associated with greater functional connectivity between semantic processing and emotion regulation areas

Abstract: Background Repetitive negative thinking (RNT), a cognitive process that encompasses past (rumination) and future (worry) directed thoughts focusing on negative experiences and the self, is a transdiagnostic construct that is especially relevant for major depressive disorder (MDD). Severe RNT often occurs in individuals with severe levels of MDD, which makes it challenging to disambiguate the neural circuitry underlying RNT from depression severity. Methods We used a propensity score, i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 117 publications
0
7
0
Order By: Relevance
“…In addition, acutely depressed patients with MDD scored significantly higher than acutely depressed BD patients when looking at more absorbing and negative emotion-focused form of ruminations, although this comparison was not significant after conducting a sensitivity analysis. A study comparing MDD patients presenting different levels of rumination (Tsuchiyagaito et al, 2022) observed that higher degrees of rumination were associated with greater connectivity between brain areas dedicated to language processing and areas involved in ER: the heterogeneity found at the level of brain connectivity may further influence the differences observed in our analyses.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, acutely depressed patients with MDD scored significantly higher than acutely depressed BD patients when looking at more absorbing and negative emotion-focused form of ruminations, although this comparison was not significant after conducting a sensitivity analysis. A study comparing MDD patients presenting different levels of rumination (Tsuchiyagaito et al, 2022) observed that higher degrees of rumination were associated with greater connectivity between brain areas dedicated to language processing and areas involved in ER: the heterogeneity found at the level of brain connectivity may further influence the differences observed in our analyses.…”
Section: Discussionmentioning
confidence: 92%
“…Changes in SMA and middle cingulate activation were also observed in MDD during reward anticipation in a meta-analysis 72 . In addition, increased connectivity in the auditory cortex, associated with repetitive negative thinking 73 , and increased activity or connectivity in the visual cortex 48,74 have also been reported in MDD.…”
Section: Discussionmentioning
confidence: 96%
“…Connectivity outside of the DMN (i.e., language and emotional salience regions) has also been suggested to differentiate individuals with high and low RNT (Tsuchiyagaito et al, 2022). Furthermore, rumination severity is not correlated with RSFC after controlling for other clinical measures of worry, whereas a worry-specific association was found after controlling for rumination (Andreescu et al, 2015), suggesting that RSFC is more closely associated with worry than rumination.…”
Section: Introductionmentioning
confidence: 99%
“…However, in contrast to the RSFC findings of increased connectivity within the DMN and between the DMN and other regions, meta- and mega-analysis studies of large cohort data have reported decreased or no difference in DMN RSFC in depressed individuals (Goldstein-Piekarski et al, 2022; Tozzi et al, 2021; Yan et al, 2019; Zhang et al, 2020). Connectivity outside of the DMN (i.e., language and emotional salience regions) has also been suggested to differentiate individuals with high and low RNT (Tsuchiyagaito et al, 2022). Furthermore, rumination severity is not correlated with RSFC after controlling for other clinical measures of worry, whereas a worry-specific association was found after controlling for rumination (Andreescu et al, 2015), suggesting that RSFC is more closely associated with worry than rumination.…”
Section: Introductionmentioning
confidence: 99%